Exploration of Alternative Therapies for the Management of Morphine Opioid Withdrawal Symptoms using Mitragyna s peciose Compound Compared with naloxone at the Mu Opioid Receptor: In Silico Approach and Molecular Docking - Sudarwati, Tri Puji Lestari; Djati, Muhammad Sasmito; Warsito, Warsito; Widyarti, Sri (Journal of Neonatal Surgery, 2025)
The current study elucidates the molecular pharmacodynamics of alkaloids derived from Mitragyna speciosa as candidates for mitigating opioid withdrawal symptoms, considering their interaction with the Mu Opioid Receptor (MOR). Employing an integrative in silico approach—including LC-MS/MS chemical profiling, ADMET prediction, molecular docking, and molecular dynamics simulation—we identified Corynoxine B as a lead compound exhibiting the most favorable binding affinity (-8.5 kcal/mol) relative to morphine and naloxone. Despite its superior affinity, Corynoxine B demonstrated comparatively lower structural stability in dynamic simulation, indicating the need for structural optimization. These findings suggest a differentiated interaction mechanism that could minimize conventional opioid side effects while maintaining therapeutic efficacy. Further in vivo and structure-activity relationship (SAR) studies are warranted to validate pharmacokinetics, receptor selectivity, and safety profiles. This work contributes to the rational development of plant-based modulators of MOR as novel alternatives or adjuncts in the clinical management of opioid dependence